Analisis Framing Pada Pemberitaan Bobby Nasution Menangani Sampah Di Medan - Oktarina, Elza Savira (Universitas Sultan Ageng Tirtayasa, 2022)
The purpose of the study was to determine Robert Entman framing analysis in framing a news story. Robert framing analysis contains four aspects: define the problem, diagnose cause, make moral judgment, treatment recommendations . News in this study on the handling of garbage in medan city by Bobby Nasution. The methods in this study use qualitative descriptive methods. The news sources in this study came from two online media, namely Liputan 6 and Medanposonlien.com. with news topics about the seriousness of the Mayor of Medan in dealing with the problem of garbage in Medan City. The framing results of both online media are different from the way news is packaged. Liputan 6 frames the technological aspects of ALFIMER, while Medanposoline.com contains handling actions by Bobby Nasution.